Application of Chain Nursing Process in the Nursing of Elderly Inpatients with Implantable Venous Infusion Port - Juan Hu; Li Zhou; Juanying Ding (Emergency Medicine International)
Objective. To explore the application effects of chain nursing process in the nursing of elderly inpatients with implantable venous infusion port. Methods. 81 elderly inpatients who were treated with implantable venous infusion port in the hospital were selected between February 2018 and December 2021, and they were divided into the routine group (given routine nursing of implantable venous infusion port, n = 40) and the study group (given chain nursing process intervention on the basis of the routine group, n = 41) according to the random number table method. The patients in both groups were intervened for 1 month. The catheter-related indicators and incidence rates of adverse events (drug extravasation, local hematoma, infusion port blockage, catheter-related infection) were compared between the two groups of patients. Generalized Anxiety Disorder 7-item scale (GAD-7) and Athens Insomnia Scale (AIS) were used to compare the psychological states of the two groups before and after intervention, and Newcastle Satisfaction with Nursing Scale (NSNS) was adopted to compare the nursing satisfaction of patients before and after intervention. Results. After intervention, the catheter maintenance operation time in the study group was shorter than that in the routine group (P<0.05), and there were no significant differences in the accidental extubation rate and re-intubation rate between the two groups (P>0.05). The incidence rate of adverse reactions of 2.44% in the study group was lower than 15.00% in the routine group (P<0.05). After intervention, the scores of GAD-7 and AIS in the two groups were reduced compared with those before intervention, and the above scores in the study group were lower than those in the routine group (P<0.05). Before intervention, there were no significant differences in the NSNS scores between the two groups (P>0.05). After intervention, the NSNS scores in the study group were higher than those in the routine group (P<0.05). Conclusion. Chain nursing process can help to enhance the maintenance quality of implantable venous infusion port, reduce the incidence of adverse events, relieve the tension and anxiety, and improve the satisfaction of patients with nursing.